(untitled) (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT Pemayun Temple in Banjar Tegal Village, is a temple that has many uniqueness including the structure of the Pemayun Temple building, the existence of educational values seen from the many community activities related to Hindu Religious Education conducted at Pemayun Temple. The problems to be studied in this research are (1) the structure of Pemayun Temple, (2) the function of Pemayun Temple as a medium of education and (3) the potential of Pemayun Temple as a medium of education. While the purpose of this research is to know the structure of Pemayu Temple building, the function of Pemayun Temple as a medium of education and to know the potential of Pemayun Temple as a medium of education. The theories used in this research are structuralism, theory of education as a system and value theory. The structure of Pemayun Temple consists of (1) nista mandala or jaba side there is a bentar temple building, and pelinggih lebuh. (2) madya mandala / middle jaba there is a Pelinggih Ratu Ngurah Demung and Demang, there is a bale kulkul, bale pebatan, pewaregan, warehouse, paduraksa. (3) The main mandala/offal has bale pengenem, paruman, 18 pelinggih, Bale Pegongan and Gedong Simpen. The function of Pemayun Temple as an educational medium is to have a religious function, social function, ethical function and function as cultural preservation.. With the potential of Pemayun Temple as a medium of education can shape the socio-cultural behavior of the community.